"Brave men" and "emotional women": A literature review on gendered norms towards patients with pain. (13th November 2019) - Samulowitz, A; Gremyr, I; Eriksson, E; Hensing, G
Abstract: Background: More women than men report chronic pain but despite the large body of research on sex differences there is a lack of knowledge on the influence of social and cultural gender. As gender norms can lead to gender bias in health care it is important to raise awareness about them. The purpose of this study was to illustrate gendered norms about men and women with chronic pain in scientific journals, and to analyze how societal norms are reproduced in health care. Methods: A literature search of the databases PsycINFO, CINAHL and PubMed was conducted, January 2000 to April 2015, with the search term chronic pain combined with femininity, masculinity, gender bias, gender stereotypes and gender roles. A total of 77 articles met the inclusion criteria and were analyzed qualitatively. The integrative approach enabled a review of articles from both social and medical sciences, and to include qualitative and quantitative research. The material was sorted into theoretical categories and further coded into substantive categories. Results: The included articles showed a variety of gendered norms about men's and women's experience and expression of pain, their identity, lifestyle and coping style. Women were described as emotional and hysterical, constantly dealing with mistrust from health care. Men were pictured as brave, stoic and struggling with their sense of masculinity. Prevailing societal norms are consolidated in health care, positioning the masculine man as the ideal patient. Conclusions: Gender stereotypes are reproduced in healthcare, which can lead to gender bias in the treatment of patients with pain. The findings were used to develop a tool, "the pain cube", aimed to improve health care providers' consciousness about gendered norms. Key messages: Men and women with chronic pain are depicted in a stereotypical way in scientific articles. Increased awareness about gendered norms can support health care professionals in providing equitable care.